Perinatal IV Aluminum and Developmental Delay - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The effect of perinatal exposure to intravenous aluminum on the neurologic development of 227 premature infants (<34 weeks gestation, <1850g weight) from the neonatal intensive care unit of Rosie Maternity Hospital, Cambridge, UK was studied at the Dunn Nutrition Unit, Cambridge, and the Institute of Child Health, London.